Legitimacy of Social Justice in the Terrorism Regulations: Insight from Several Countries - Ali Masyhar; Rohadhatul Aisy; Akhmedova Mehrinigor Bahodirovna; Gaini Mukhanova (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2024)
Indonesia continues to experience recidivist terrorism regularly as a result of the injustices it faces. As a result, it is critical to prioritize the legitimacy of social justice for both victims and perpetrators, as well as adopt a humanitarian approach to non-criminal terrorism to mitigate and avert criminal acts of terrorism. This research aims to analyze the legitimacy of social justice in counterterrorism environments. This research employs normative juridical research to compare the counterterrorism regulations of several countries that incorporate social justice legitimacy. The findings of this research show that, first, it is crucial to integrate procedural justice and legitimacy principles into counterterrorism initiatives to preserve public confidence in the justice system, prevent exploitation, and uphold human rights. Second, it is critical to compare other countries' terrorism regulations to understand and evaluate their strategies for enhancing international cooperation and preventing terrorist attacks. In response to persistent terrorist threats, the United Kingdom, Pakistan, and the European Union implemented more ambitious counterterrorism strategies and incorporated social justice into their policies. To achieve effective and socially just terrorism regulations, Indonesia must adopt regulations in these countries.